THE STRUGGLE BETWEEN SALAFI SCHOLARS AND ISLAMIC BOARDING SCHOOL SCHOLARS: THE CONTROVERSY OVER THE PRACTICE OF FIQH HADITH IN ACEH AND NORTH SUMATRA, INDONESIA - Tarmizi M. Jakfar; Nurdin Bakry; Safria Andy; Muhammad Habibi MZ (Universitas Islam Negeri Ar-Raniry, 2023)
The Da'wah of the Salafi School aims to purify Islamic teachings by eradicating all kinds of deviations from Islamic practices that have mixed with non-Islamic cultures, giving rise to bid'ah. The salafi school invites them to return to the Al-Qur'an and hadith, where hadiths are only understood textually and in their sermons the salafi scholars openly attack Islamic boarding school scholars. ? How is the resistance carried out by Islamic boarding school scholars to salafi preaching, especially in understanding hadith? What is the influence that occurred on the implementation of Fiqh by the people in Aceh and North Sumatra Medan? This research is qualitative, namely a way of research and understanding that is based on how to investigate environmental conditions and community problems. The method of qualitative research is usually stated as a naturalistic research method because the research is carried out when the circumstances are as they are, also known as the ethnographic method. The approach used is an anthropological approach. To get the data, structural analysis, historical analysis, and ideological criticism were carried out. Based on the results of the research, it can be seen that the proselytizing of the Salafi sect which is carried out by attacking Islamic boarding school scholars openly, aims to really practice shari'ah which has the basis of Rasulullah SAW. Because they think that the Islamic boarding school scholars have left the Sunnh of Rasulullah SAW, so if it is not sunnah, don't do it because it will enter into bid'ah acts. However, the method adopted by the Salafi sect has actually departed from the provisions of the Koran itself, which wants da'wah to be carried out gently. Islamic boarding schools/dayah scholars should show their resistance to the salafi school (wahabi), because the salafi school is wrong in understanding hadith, because it only relies on textual understanding. Whereas hadith as the second source of Islamic law must be understood correctly, both textually and contextually, so that the messages of the Messenger of Allah through hadith, especially in interpreting the verses of the Koran which are still common, reach the community correctly. Salafi da'wah carried out both in Aceh and in North Sumatra has not had an impact on the community in practicing fiqh as expected by the salafi sect, because the community still commemorates Islamic holidays and understands hadith based on the Shafi'i school of thought. It is hoped that the salafi sect will carry out da'wah in ways that are gentle and willing to communicate in two directions, so that the messages to be conveyed can be accepted by the community. It is hoped that Islamic boarding schools/dayah scholars will maintain communication with the Salafi school, so that divisions can be avoided in an effort to maintain unity among fellow Muslims. It is hoped that the community will always maintain conditions so that they remain conducive even though they face ridicule and insults in practicing fiqh in everyday life.